The ethics of management - Hosmer, LaRue Tone (McGraw-Hill/Irwin, 2006)
It is often said that ethics is essential for leadership; Hosmer argues that leadership is also essential for ethics. The theme of "The Ethics of Management, Sixth Edition", is that business firms today operate in a competitively intense, technologically complex and culturally diverse global economy. Pressures to dodge issues and cut corners are greater than ever before. "The Ethics of Management" by LaRue Hosmer provides a very explicit three-part framework to analyze those problems by combining economic outcomes, legal requirements and ethical principles. Students will learn how to convincingly present their moral point of view to others in order to jointly serve their companies, protect their careers, and improve their societies.